“Análisis comparativo de los ide’s de desarrollo xamarin visual studio vs android studio aplicado al sistema de notificación de actividades de la UNACH, 2017” - Santos Galán, Alexis Daniel (2018)
The present research had as objective to compare the development IDE’s Xamarin visual studio vs. Android Studio applied to the system of the activities notification at UNACH. The type of the study was not experimental. Besides it is transversal because it is a comparison of independent samples in a one moment. The research was descriptive an applied because it is intended to solve an existing problem; the method used was deductive and analytical because the object of study will be separated to study it individually. It was made measurements during a week in the selected mobile which is a Samsung J/ prime, the same that has installed two similar applications developed in different IDES’S it was used the benchmark that comes by default in the new versions of Android, which measures the performance of this, a large number of measurements was obtained in the established time period. In this case a non-random sample of an infinite population was determined, the data was migrated to the IBM SPSS statistical software, the statistic to be applied was Mamn-Whitney U because through the software it was found that the data are not normalized, At the end the null hypothesis was rejected, and the researcher hypothesis was approved which indicates that “there are differences in performance between Xamarin Visual Studio and Android Studio”. It is concluded that Android is 1.19% more efficient in the use of the memory of the device and 0.04% in the use of the CPU